Reconstructing the Ministry of Communication and Digital’s Image in the TikTok Live Controversy - Solihah, Sopiyani; Wijayanti, Yani Tri (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2026)
Freedom of expression in Indonesia is regulated under Article 28E (3) of the 1945 Constitution. On September 3, 2025, the Indonesian government disabled the live broadcast feature on the TikTok platform while the August 25, 2025 demonstration was still ongoing. This decision sparked public perception of restrictions on freedom of expression through digital media, because social media, including TikTok's live feature, is used by the public to share situations in real time. This phenomenon placed the Ministry of Communication and Digital Affairs (Komdigi) under public scrutiny and triggered a crisis. This study aims to analyze Komdigi's crisis communication strategy, as it directly relates to the sustainability of public trust, policy legitimacy, and the effectiveness of government functions in a digital era.. This study uses quantitative content analysis with research objects in the form of news published by detik.com during the period of August 26 to September 3, 2025. The results show that Komdigi predominantly used the Denial strategy with a percentage of 100%, meaning that in all 10 news articles containing Komdigi's response to the crisis, Komdigi consistently provided denials or rejections. Other strategies included Evasion of Responsibility (60%), Corrective Action (70%), and Reducing Offensiveness (90%). Meanwhile, this study found no use of the Mortification strategy, which was recorded at 0%. Overall, Komdigi relied heavily on denial, while simultaneously attempting to reduce allegations, reducing negative perceptions, promising improvements, and avoiding direct responsibility without apologizing.